Object of Onomastic Research (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Onomastics is a branch of linguistics that studies any famous names, the history of their origin and change, as well as the sum of all famous names. In some studies, the term “onomastics” is also used in the sense of anthroponymy. Onomastics aims to identify and study existing onomastic systems.